Servant Leader’s Characteristics: Implications for Youth Christian Leaders in FS Community - Ivana Krisantana (IPTEK Journal of Proceedings Series, 2020)
The world knows many types of leadership, one of which is servant leadership pioneered by Greenleaf (1977). According to Spears (2010), servant leadership has 10 main characteristics that make it unique. These characteristics enable a leader to focus on his/her followers and strive to make them grow better, unlike other leadership styles that focus on organizational interests and goals (Rachmawati and Lantu, 2014). This practice of servant leadership started by Jesus Christ continues to be emulated and lived by many figures after Him. Unfortunately, not all people who claim to be Christians (followers of Christ) actually become servant leaders. This study aims to explore whether the main characteristics of servant leadership really emerge in leaders and still relevant to be practiced in church life today. We will focus on exploring servant leadership practices at FS Community, the youth community of GKA Gloria Pacar, using observation, interview, and document analysis. The ten characteristics that discussed in this research are listening, empathy, healing, awareness, persuasion, conceptualization, foresight, stewardship, commitment to the growth of people, and building community. These are not a requirement that all must be prominent in each leader, but rather are the traits of servant leaders. It means, the more these characters are seen in a person, the more he/she has a heart that is willing to serve, and the closer he/she is to the picture of a perfect servant leader. Although perfection is not possible because we are only limited human beings, these ten characters must be a dream to be pursued by leaders who claim themselves as servant leaders.